A systematic review and network meta‐analysis comparing Rezūm with transurethral needle ablation and microwave thermotherapy for the management of enlarged prostate - Ansh Bhatia; Joao G. Porto; Renil S. Titus; Vishal Ila; Khushi Shah; Ankur Malpani; Diana M. Lopategui; Robert Marcovich; Thomas R. W. Herrmann; Hemendra N. Shah (BJUI Compass)
Abstract Objectives We aim to compare efficacy and safety of water vapour therapy (Rezūm), transurethral needle ablation (TUNA) and transurethral microwave therapy (TUMT) for treating men with moderate to severe benign prostatic hyperplasia (BPH) symptoms. Materials PubMed/MEDLINE, EMBASE and Cochrane Library were searched from inception to 30 July 2023, followed by reference searching and dual‐independent study selection. We analysed only randomized clinical trials. RoB‐2, NIH‐quality assessment tool and GRADE guidelines were used for quality‐of‐evidence (QoE) assessment. Relevant prospective studies without a critical risk‐of‐bias were included. Results At 12 months, Rezūm showed similar efficacy to TUNA and TUMT for improvement in International Prostate Symptoms Score – Rezūm versus TUMT: 1.33 points (95% CI: −1.66 to 4.35) favouring TUMT (QoE: Moderate) and Rezūm versus TUNA: 0.07 points (95% CI: −3.64 to 3.88) favouring TUNA (QoE: Low). Rezum had similar outcomes to TUNA and TUMT for Maximum Peak‐Flow Rate (Qmax): Rezūm versus TUMT: 1.05 mL/s (95% CI: −4.88 to 2.82) favouring Rezūm (QoE: Low) and Rezūm versus TUNA: 0.37 mL/s (95% CI: −4.61 to 4.21) favouring TUNA (QoE: Low). Furthermore, post‐void residual volume (PVR) comparisons demonstrated that Rezūm was similar, or inferior to other techniques at 12 months – Rezūm versus TUMT: 11.20 mL (95% CI: −32.40 to 10.30) favouring TUMT (QoE: Low) and Rezūm versus TUNA: 24.10 mL (95% CI: 2.81 to 45.10) favouring TUNA (QoE: Low). Rezūm also had a similar surgical retreatment rate with TUMT and TUNA up to 3‐years – TUMT versus Rezūm RR: 1.21 (95% CI: 0.20 to 15.90) (QoE: Low) and TUNA versus Rezūm showed RR: 1.81 (95% CI: 0.2 to 24.60) (QoE: Low). In the first 12 months after treatment, Rezūm had a higher rate of serious adverse events (Clavien‐Dindo ≥ Grade 3) than TUMT and TUNA. TUMT versus Rezūm with RR = 0.53 (95% CI: 0.13 to 3.14) (QoE: Low) and TUNA versus Rezūm with RR = 0.38 (95% CI: 0.04 to 3.49) (QoE: Low). Conclusions Moderate to weak evidence suggests that Rezūm is not superior to TUNA and TUMT in all domains studied.